Biophysical characterization of branched amphiphilic peptide capsules and their potential applications in radiotherapy - Sukthankar, Pinakin Ramchandra (Kansas State University, 2014)
Branched Amphiphilic Peptide Capsules (BAPCs) are peptide nano-spheres comprised of equimolar proportions of two branched peptide sequences bis(FLIVI)-K-KKKK and bis(FLIVIGSII)-K-KKKK that self-assemble in water to form bilayer delimited poly-cationic capsules capable of trapping solutes. We examined the lipid-like properties of this system including assembly, fusion, solute encapsulation, and resizing by membrane extrusion as well as their capability to be maintained at a specific size by storage at 4˚C. These studies along with earlier work from the lab (Gudlur et al. (2012) PLOS ONE 7(9): e45374) demonstrated that the capsules, while sharing many properties with lipid vesicles, were much more robust. We next investigated the stability, size limitations of encapsulation, cellular localization, retention and, bio-distribution of the BAPCs. We demonstrated that the BAPCs are readily taken up by epithelial cells in culture, escape or evade the endocytotic pathway, and accumulate in the peri-nuclear region where they persist without any apparent degradation. The stability and persistence of the capsules suggested they might be useful in delivering radionuclides. The BAPCs encapsulated alpha particle emitting radionuclides without any apparent leakage, were taken up by cells and were retained for extended periods of time. Their potential in this clinical application is being currently pursued. Lastly we studied the temperature dependence of capsule formation by examining the biophysical characteristics of temperature induced conformational changes in BAPCs and examined the structural parameters within the sequences that contribute to their remarkable stability. A region in the nine-residue sequence was identified as the critical element in this process. The ability to prepare stable uniform nano-scale capsules of desired sizes makes BAPCs potentially attractive as delivery vehicles for various solutes/drugs.
Keywords: PeptideBAPCs; Radiotherapy; Alpha particle; Nanocapsules; Drug delivery; Biochemistry (0487); Biophysics (0786); Biophysics, Medical (0760); Chemistry (0485); Chemistry, Radiation (0754)